2017 IEEE International Conference on Smart Grid and Smart Cities (ICSGSC) 2017
DOI: 10.1109/icsgsc.2017.8038595
|View full text |Cite
|
Sign up to set email alerts
|

Traffic event detection framework using social media

Abstract: Traffic incidents are one of the leading causes of non-recurrent traffic congestions. By detecting these incidents on time, traffic management agencies can activate strategies to ease congestion and travelers can plan their trip by taking into consideration these factors. In recent years, there has been an increasing interest in Twitter because of the real-time nature of its data. Twitter has been used as a way of predicting revenues, accidents, natural disasters, and traffic. This paper proposes a framework f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 10 publications
(13 reference statements)
2
21
0
Order By: Relevance
“…A range of technologies is contributing to the development of these smart systems. These include the Internet of Things (IoT) [32][33][34][35][36], social media [21][22][23]37,38], big data [39][40][41][42][43][44], high performance computing (HPC) [45][46][47][48], cloud, fog, and edge computing [34,[49][50][51][52], and machine learning [36,53]. The applications include healthcare [34,39,[54][55][56], transportation [57,58], and others [59,60].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of technologies is contributing to the development of these smart systems. These include the Internet of Things (IoT) [32][33][34][35][36], social media [21][22][23]37,38], big data [39][40][41][42][43][44], high performance computing (HPC) [45][46][47][48], cloud, fog, and edge computing [34,[49][50][51][52], and machine learning [36,53]. The applications include healthcare [34,39,[54][55][56], transportation [57,58], and others [59,60].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The challenges in this respect include management, integration, and distributed computation of data including the difficulties related to managing the 4V characteristics of big data, i.e., volume, velocity, variety, and veracity. There have been some works on the use of big data platforms in Twitter data analytics in various languages but in different application domains [18][19][20][21][22][23]37,78,79]. To the best of our knowledge, no work has been reported that uses big data technologies for data analytics in healthcare using tweets in the Arabic language.…”
Section: Research Gapmentioning
confidence: 99%
“…Beyond detection of disasters -traffic events, congestion, and accidents are also highly popular research applications of social media data in the transport field -see for examples (Gong and Sinnott 2015;Gu, Qian, and Chen 2016;Salas et al 2017;Tejaswin, Kumar, and Gupta 2015;D. Wang et al 2014).…”
Section: Related Workmentioning
confidence: 99%
“…Today's social sensors are widely used to solve problems [5]. Social sensors derived from computing social networking data that generally contain a variety of information related to real life [6]. Twitter is one of the social media that is widely used by the people of Indonesia [7].…”
Section: Introductionmentioning
confidence: 99%